Effects of Alkali Treatment on the Mechanical Properties and Moisture Absorption Behavior of Flax/polypropylene Composites - Xiong Xiao; Mingyang Cheng; Yucheng Zhong (Journal of Natural Fibers, 2022)
Flax fiber is one of the strongest natural fibers. However, it is highly susceptible to moisture absorption and has poor adhesion with polymer matrix. Alkali treatment of flax fiber was considered in this study aiming to overcome this issue. Four alkali solutions with different NaOH concentrations, i.e., 1 wt. %, 5 wt. %, 10 wt. %, and 15 wt. %, were prepared covering both low and high concentrations. It is successfully demonstrated that polypropylene composites reinforced by alkali-treated flax fibers not only absorbed less moisture but had better tensile and bending properties. At a NaOH concentration of 5 wt. %, maximum decrease in moisture absorption and optimum improvement in mechanical properties were simultaneously achieved. Further increase in NaOH concentration resulted in degradation of both hygrothermal durability and mechanical properties. The underlying mechanisms were comprehensively explored considering both compositional and microstructural changes due to alkali treatment.